"A Literature Review on Differentiated Instruction Based on Visual, Auditory, and Kinesthetic (VAK) Learning Styles" - Ilham Wahyudi (Jurnal Ilmiah Pendidikan dan Pembelajaran Matematika, 2025)
This study aims to examine the implementation of differentiated instruction within the context of the Merdeka Curriculum through a literature review. This approach tailors learning to students' needs, interests, and visual, auditory, and kinesthetic (VAK) learning styles. Analysis of five national articles shows that differentiated instruction enhances student interest, understanding, and participation. However, the studies lack in-depth discussion on four key elements: content, process, product, and learning environment, as well as detailed characteristics of each learning style. Further research is needed for optimal application. Differentiated instruction is considered a promising approach to support personalized learning in line with the Merdeka Curriculum.Keywords: differentiated instruction, VAK learning styles, Merdeka Curriculum, literature review, inclusive education.